(untitled) (The Pakistan Development Review, 2006)
Potato (L. Solanum tuberosum) belongs to Solanaceae family. It is the most important dicotyledonous tuber crop and possesses major socio-economic importance worldwide. It is the fourth most cultivated food crop after wheat, rice and maize in world. Potato is a good and cheaper source of carbohydrates, vitamins, minerals and proteins and also provides most of the trace elements, which can meet the energy requirement of the people living in the developing countries like Pakistan [Rahman (1986)]. About 325 million metric ton of potato is produced annually throughout the world [World Book (2001)]. This crop is financially more remunerative than cereals from food security and can be recommended as a partial replacement of cereals.